Dreamcatcher - Ian Evans Guthrie (Journal of the Association for Technology in Music Instruction, 2025)
Dreamcatcher is a composition for piano and fixed media. Dreamcatcher is the organic result of a commission from and collaboration with a contemporary choreographer. Approached at a recent summer camp about composing music for a “dreamy” choreography, it became a work that synthesizes the sounds of our environment, the subconscious of sleep, the nostalgia of a cleaner world, and the hope of a better future.